Public Health Strategy of Tuberculosis in Bangladesh: A Review Update - Mary, Rabeya Mashferat; Hasan, Jahid (Bangladesh Journal of Infectious Diseases, 2025)
Tuberculosis is a major public health concern in Bangladesh. Government struggles financially to establish treatment centers despite getting financial aids from NGOs. The high number of tuberculosis deaths in Bangladesh results from delays in the treatment process. Increased funding to allow the purchase of more drugs is a vital requirement to be facilitated by the Government of Bangladesh treasury. Strong-collaboration with WHO and international NGOs offering to help the TB incidences treatment in Bangladesh. Bangladesh Journal of Infectious Diseases, December 2024;11(2):160-165